Hand grip strength and depression among rural older South Africans - Peltzer, Karl (Humanitas: Indonesian Psychological Journal, 2022)
The study aimed to assess the relationship between hand grip strength (HGS) and depressive symptoms among ageing women and men in a longitudinal study in rural South Africa. We analyzed longitudinal data from two consecutive population-based surveys in Agincourt, South Africa, 2014/2015-2018/2019. Results indicate that in all, 835 adults of 3268 participants without depression in Wave 1 (25.0 percent) had incident depression in Wave 2, and 184 adults of 3866 participants who had depression in Wave 1 (4.8 percent) screened positive for depression at both Wave 1 and 2 (persistent depression). The prevalence of weak HGS was 51.5 percent at baseline. In the fully adjusted model, weak HGS increased the odds of incident depressive symptoms between both sexes (AOR: 1.24, 95 percent CI: 1.04-1.47) among women (AOR: 1.33, 95 percent CI: 1.05-1.68), but not among men. No models among both sexes, among men and women, showed an increased odds of weak HGS with persistent depressive symptoms. Weak HGS was independently associated with the incident, but not persistent depressive symptoms between the two sexes and between women but not between men